Dietary Treatment of Epilepsy : a Practical Guide. - Neal, Elizabeth (Wiley, 2012)
Epilepsy is a common chronic neurological disorder characterised by recurrent unprovoked seizures, and affects 50 million people worldwide. Approximately 30% of these do not have seizure control even with the best available medications, hence renewed and increasing interest in the use of dietary treatments to treat epilepsy. These treatments include the traditional ketogenic diets but also the newer modified Atkins diet and low glycaemic index treatment. The ketogenic diet is a high-fat, adequate-protein, low-carbohydrate diet that in medicine is used primarily to treat refractory ep.